THE INFLUENCE OF FRAUD PENTAGON ON FRAUDULENT FINANCIAL STATEMENTS - Irman, Mimelientesa; Sugestih, Dea' Stri; Suriyanti, Linda Hetri (Bilancia : Jurnal Ilmiah Akuntansi, 2025)
This research aims to determine the influence of Pentagon Fraud in the face of Fraudulent Financial Statements on Banking subsector companies that have registered on the IDX in the period 2019 to 2023. This research uses secondary data with a sampling technique in the form of purposive sampling. The sample used in the scope of this research is 33 companies. This research uses tools for analysis in the form of Smart PLS 4.0 software. The results of the scope of research carried out provide an indication that there is a positive and significant influence on Financial Stability and Director Change in the face of Financial Statement Fraud, Ineffective Monitoring and Changes Auditors do not have a negative and not significant influence in the face of Financial Statement Fraud. Meanwhile, there is a significant and negative influence on Frequent Number of CEO picture in the face of Financial Statement Fraud. Penelitian ini bertujuan untuk mengetahui pengaruh Fraud Pentagon dalam menghadapi Fraudulent Financial Statement pada perusahaan subsektor Perbankan yang telah terdaftar di BEI pada periode tahun 2019 sampai dengan tahun 2023. Penelitian ini menggunakan data sekunder dengan teknik pengambilan sampel berupa purposive sampling. Sampel yang digunakan dalam lingkup penelitian ini sebanyak 33 perusahaan. Penelitian ini menggunakan alat bantu untuk analisis berupa software Smart PLS 4.0. Hasil penelitian yang dilakukan memberikan indikasi bahwa terdapat pengaruh positif dan signifikan terhadap Stabilitas Keuangan dan Pergantian Direksi dalam menghadapi Fraudulent Financial Statement, Ketidakefektifan Monitoring dan Pergantian Auditor tidak memiliki pengaruh signifikan terhadap Frequent Number of CEO picture dalam menghadapi Financial Statement Fraud.